Desain dan Implementasi Algoritma Korelasi Daya dan Tegangan di Kapasitor untuk Maximum Power Point Trackking pada Photovoltaic Menggunakan Arduino Uno - Pratomo, Leonardus Heru; Riyadi, Slamet (Jurnal Teknik Elektro, 2020)
Photovoltaic is a main device in solar power generation systems. The performance of this component needs to be improved to get the maximum power point. Many methods for maximizing power in photovoltaic have been developed and implemented in various algorithms. In fact, the algorithm has a lot of complexity and it requires a signal processing system that has a high speed and expensive one in the implementation. To overcome this problem, an algorithm based on power and voltage correlation inthe capacitors is developed to get maximum power. If the voltage across the capacitor is controlled according to the maximum power point voltage (VMPP), the maximum power (PMPP) value would be achieved. This concept is verified through computational simulations anda voltage control algorithm would be implemented using the Arduino Uno microcontroller for the final verification. The efficiency of the simulation is 99.88%–99.92% and an experimental is 92.84%–94.78%.